Graph algorithms and applications 2 - Liotta, Giuseppe; Tamassia, Roberto, 1960-; Tollis, Ioannis G., 1958- (World Scientific, 2004)
This book contains Volumes 4 and 5 of the Journal of Graph Algorithms and Applications (JGAA). The first book of this series, Graph Algorithms and Applications 1, published in March 2002, contains Volumes 1-3 of JGAA. JGAA is a peer-reviewed scientific journal devoted to the publication of high-quality research papers on the analysis, design, implementation, and applications of graph algorithms. Areas of interest include computational biology, computational geometry, computer graphics, computer-aided design, computer and interconnection networks, constraint systems, databases, graph drawing, graph embedding and layout, knowledge representation, multimedia, software engineering, telecommunications networks, user interfaces and visualization, and VLSI circuit design. The journal is supported by distinguished advisory and editorial boards, has high scientific standards, and takes advantage of current electronic document technology. The electronic version of JGAA is available on the Web at http:/ /jgaa.info/. Graph Algorithms and Applications 2 presents contributions from prominent authors and includes selected papers from the Dagstuhl Seminar on Graph Algorithms and Applications and the Symposium on Graph Drawing in 1998. All papers in the book have extensive diagrams and offer a unique treatment of graph algorithms focusing on the important applications.